2013
DOI: 10.1021/ic3019698
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Valence and Structural Changes in YbMn2Ge2—Inelastic X-ray Spectroscopy and Theoretical Investigations

Abstract: The pressure-induced valence change of Yb in YbMn(2)Ge(2) has been studied by high pressure inelastic X-ray emission and absorption spectroscopy in the partial fluorescence yield mode up to 30 GPa. The crystal structure of YbMn(2)Ge(2) has been investigated by high pressure powder X-ray diffraction experiments up to 40 GPa. The experimental investigations have been complemented by first principles density functional theoretical calculations using the generalized gradient approximation with an evolutionary algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Resonant Inelastic X-ray Scattering (RIXS) measurements are bulk sensitive and constitute an excellent probe to determine valence changes under extreme conditions. [11][12][13] Our experiments and calculations show that the Eu valence sharply increases on application of pressure to a nearly trivalent state above 9 GPa at 10 K. Further, this sharp increase in valence is found to occur around the critical pressure where a structural transition to a collapsed tetragonal (CT) phase is observed.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Resonant Inelastic X-ray Scattering (RIXS) measurements are bulk sensitive and constitute an excellent probe to determine valence changes under extreme conditions. [11][12][13] Our experiments and calculations show that the Eu valence sharply increases on application of pressure to a nearly trivalent state above 9 GPa at 10 K. Further, this sharp increase in valence is found to occur around the critical pressure where a structural transition to a collapsed tetragonal (CT) phase is observed.…”
mentioning
confidence: 69%
“…The self-interaction corrected local spin density (SIC-LSD) approximation 13 effective Eu valence, similar to the previous applications to Yb compounds. 12,13 The SIC-LSD method was implemented with the linear muffin-tin orbital method 17 using the atomic spheres approximation, by which the crystal volume is split into slightly overlapping spheres centered on the nuclear positions. In these calculations, a ferro-magnetic ordering of Eu moments was adopted.…”
mentioning
confidence: 69%
“…19 However, in one run, multiple XANES scans were collected during cooldown, and a large change in the edge was noted between about 250 and 150 K. Further investigation showed that a large valence reduction only occurs near 200 K and is extremely unusual. Reversible valence changes may occur when samples are damaged; 40,41 also, large increases in valence have been observed under high pressure, 42 but not a valence decrease.…”
Section: ■ Resultsmentioning
confidence: 99%
“…We show that the Yb effective valence at room temperature is sensitive to pressure, with a value of v = 2.72(2) at ambient pressure, and approaches near trivalency, v = 2.93(3) at pressures above 9 GPa. However, the pressure–volume (PV) relation shows no peculiarities associated with the pressure-induced valence transition, which is in contrast to the case of YbMn 2 Ge 2 , where a similarthough more abruptvalence transition is seen in association with a distinct anomaly in the PV relation …”
Section: Introductionmentioning
confidence: 81%
“…In PFY-XAS scans the intensity of the emitted Yb Lα fluorescence was measured while scanning the energy of the primary beam. RXES has been applied to investigate a variety of Yb intermetallic and other heavy fermion compounds. RXES enables the valence to be determined with incident photon energies being selected to enhance signals from different valence states. To further analyze the experiments electronic structure calculations have been performed for YbFe 2 Ge 2 using the self-interaction corrected local spin-density (SIC-LSD) method. , This ab initio electronic structure method allows studying the pure divalent and trivalent states of Yb as well as an approximate model of the intermediate valence state.…”
Section: Introductionmentioning
confidence: 99%